Analisis Tingkat Kesehatan Keuangan PT. Bank Central Asia Tbk Periode 2022–2024 Menggunakan Metode Camel - Abdulloh Faqih Satrio Wibowo; Hillary Stefany Tallo; Elbertus Ranse Panshar; Yudika Putra Koten; Wilhelmus Giovanni Meak; Ade Try Pratama; Patricia Clarissa Whitney Kabosu; Anggraeni Natasya Dethan; Marshanda Irnel Cantika Nara Kaha; Cheny Sanggryla Babu Dao; Oktavianye Eka Putri Huky; Welhelmina M. Ndoen; Agustian, Efandri (Fakultas Hukum dan Ekonomi Bisnis, 2025)
Bank financial soundness evaluation is essential for sustaining national financial stability and public confidence. As intermediary institutions, banks must maintain strong performance, robust governance, and efficient risk management. This study assesses the financial health of PT Bank Central Asia Tbk (BCA) over 2022–2024 using the CAMELS framework (Capital, Asset Quality, Management, Earnings, Liquidity, Sensitivity to Market Risk). The quantitative descriptive research uses secondary data from BCA's annual reports, analyzed via key financial ratios compared to Financial Services Authority (OJK) standards. Findings show BCA consistently rated very healthy across all CAMELS components. Strong capital (CAR >25–29%), preserved asset quality (NPL <1–2%), effective management with solid governance, high profitability (ROA 3.2–3.9%, ROE 21–24%), adequate liquidity, and low market risk sensitivity. These results underscore BCA's economic resilience, supported by prudent risk management and portfolio diversification.